Brief Report: Self‐Organizing Neuroepithelium from Human Pluripotent Stem Cells Facilitates Derivation of Photoreceptors123. (12th February 2013) - Boucherie, Cédric; Mukherjee, Sayandip; Henckaerts, Els; Thrasher, Adrian J.; Sowden, Jane C.; Ali, Robin R.
Abstract Retinitis pigmentosa, other inherited retinal diseases, and age‐related macular degeneration lead to untreatable blindness because of the loss of photoreceptors. We have recently shown that transplantation of mouse photoreceptors can result in improved vision. It is therefore timely to develop protocols for efficient derivation of photoreceptors from human pluripotent stem (hPS) cells. Current methods for photoreceptor derivation from hPS cells require long periods of culture and are rather inefficient. Here, we report that formation of a transient self‐organized neuroepithelium from human embryonic stem cells cultured together with extracellular matrix is sufficient to induce a rapid conversion into retinal progenitors in 5 days. These retinal progenitors have the ability to differentiate very efficiently into Crx+ photoreceptor precursors after only 10 days and subsequently acquire rod photoreceptor identity within 4 weeks. Directed differentiation into photoreceptors using this protocol is also possible with human‐induced pluripotent stem (hiPS) cells, facilitating the use of patient‐specific hiPS cell lines for regenerative medicine and disease modeling. STEM CELLS2013;31:408–414